Give Forests a Hand Leader Guide - Alison Bowers; Janice Easton; Martha C. Monroe; Lizzie Peme (EDIS)
This guide is adapted, with permission, from Give Water a Hand Action Guide, a youth program for local environmental action. 71996. University of Wisconsin Board of Regents. For more information on Give Water A Hand call 1-800-WATER20.